The Global Flora: Descriptive statistics with a commentary and an ethnobotanical example - Moerman, Daniel (Ethnobotany Research and Applications, 2013)
This paper briefly describes the world’s flora, based on the materials available at ThePlantList.org, a large web site built by a collaboration of botanists at Kew Gardens and the Missouri Botanical Garden. The paper details the number and distribution of families, genera, species, authors, publication dates and several other elements of the flora. The author notes several of the most notable features of this global scientific enterprise. Though it might seem arcane, the database is widely utilized, and as such seems worth examining. For example, a search of Wikipedia.com found 901 references to ThePlantList.org.